Reflections on Neuroethical Issues in Neuroimaging Research Advances from the Islamic Perspective - Nurfaizatul Aisyah, Ab Aziz; Muzaimi, Mustapha; Sabarisah, Hashim (Universiti Kebangsaan Malaysia, 2024)
The growth of neuroscientific research from the progress of neurotechnologies imposed an evolving range of potential bioethical issues. In this context, neuroethics offers insightful guides for researchers to deal with such emerging ethical issues in neuroscience research. However, with diverse brain-related research areas worldwide, potential frictions on moral and ethical grounds are likely to surface which inevitably compounded by local traditions and/or belief systems. Potential ethical issues may originate from shared or distinct perspectives depending on the region that can vary from histories, philosophies, moral values, and social stances. Herein, we focused on Islam as the second-largest religious group globally with such diversities. This narrative review aims to highlight the potential neuroethical issues arising from the advances of neuroimaging in neuroscience research from an Islamic perspective through the lens of Islamic legal maxims (al-qawa`id al-fiqhiyyah)